Leader Member Exchange sebagai Pemoderasi dalam Hubungan Stress Kerja, Lingkungan Kerja dan Beban Kerja terhadap Turnover Intention (Studi pada Garuda Plaza Hotel Medan) - Retno Dwi Pratiwi (Universitas Harapan Medan, 2020)
Garuda Plaza Hotel is one of the companies in the city of Medan that is well known and quite attractive to the people of Medan. With competition the increasing number of other companies in the city of Medan has become a potential opportunity that must be developed by the Garuda Plaza Hotel to become a company that remains in the forefront. The purpose of this study was to determine the effect of work stress, work environment and workload partially on Turnover Intention at Garuda Plaza Hotel Medan and to find out whether the leader member exchange strengthens the relationship between work stress, work environment and workload partially on Turnover Intention on Garuda Plaza Hotel Medan. This type of research is causal research. The population in this study is the number of employees of Garuda Plaza Hotel Medan, amounting to 241 people and the sample used in this study were 100 people using the Slovin method. Data analysis techniques in this study are regression and MRA. The results showed that work stress had no effect on Turnover Intention, the work environment had a positive and significant effect on Turnover Intention and workload had a positive and significant effect on Turnover Intention. Work stress, work environment and work load simultaneously have a significant effect on Turnover Intention.